Pengaruh Supervisi Akademik dalam Meningkatkan Kinerja Guru di SMP Negeri 27 Kota Bekasi - Kasmawati, Lia Wati (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2024)
This research aims to prove that there is a significant relationship between principal supervision and increased teacher performance. The method used in this research is a qualitative method using a descriptive approach to describe the data results, and a qualitative survey method approach. The respondents in this research were 44 teachers at SMP Negeri 27 Bekasi City. Data collection techniques used interview, observation, documentation and instruments were developed in the form of questionnaires. The results of this research conclude that academic supervision carried out by the principal or supervisor (deputy principals) which has been carried out systematically and programmed, will have an effect on teacher performance as evidenced by the results of student scores when the teacher teaches correctly according to the supervision stages, namely 90 % of students answered questions correctly when the teacher gave a post test at the end of the lesson in supervision. so that teachers feel that there is assistance from the principal in improving their performance, teachers feel happy and motivated to continue the learning methods and stages of supervision which will always be implemented during the daily teaching and learning process, not only during the implementation of supervision, this has been proven to be widespread In a questionnaire to students, it was given that after learning was completed, students felt happy, easily accepted the lesson, the lesson was not boring by 90% compared to previous learning, students felt bored, when the teacher did not teach correctly, using the teacher's conventional method. The researchers also distributed questionnaires in the form of questions to teachers who, after being supervised, how they felt, 91% felt happy, gained new competencies and 92% of the teachers would implement learning that was pro-student in every teaching, not just in supervision activities, so that the teacher's performance in the learning process with students will increase. Academic supervision carried out by the Principal is one way to find out Teacher Performance. In academic supervision, there are two competencies that must be mastered by a teacher, namely pedagogical competency and professionalism competency, both of which are found in the academic supervision process, which will have an impact on improving the performance of teachers in schools. Factors that support the success of academic supervision are factors from the school principal and teachers being supervised. In carrying out academic supervision of teachers, school principals must know the instruments and steps in carrying out supervision. Meanwhile, the supervised teacher has the desire to improve his performance through academic supervision activities which is shown by a cooperative attitude towards the process of supervision activities, and the supervised teacher has implemented all the instruments in the supervision assessment. Supervision is not to criticize but to improve the performance competence of teaching staff.